How to Create and Moderate a Great Problem-Based Learning Discussion (PBLD) - Kirk Lalwani (Association of American Medical Colleges, 2013)
Abstract Introduction Members of the review committee for the Society for Pediatric Anesthesia (SPA) and American Society of Anesthesiologists (ASA) annual meetings regularly reject approximately 70% of problem-based learning discussion (PBLD) submissions mainly as a result of poor quality. The most common errors are that the problem either is too narrow in scope with no potential for discussion or has a lack of controversy. The author served as a reviewer on these committees and decided that disseminating the basic tenets of creating and moderating engaging PBLDs would be an effective way to improve the quality of case-based teaching in academic departments, as well as the quality of conference submissions. Methods This PBLD addresses the rationale and benefits of case-based learning, differentiates problems suitable for case-based learning from those more appropriate for a case report, provides a framework for participants to construct an engaging PBLD from a brief stem, and outlines best practices for moderating a PBLD. After the case presentation, the instructor guides the group through a series of questions, each of which promotes discussion, and reviews the recommended strategies for the relevant aspect of the teaching method. Following the discussion, time is devoted to evaluation of the session and feedback from participants. Results The idea for this PBLD is based on workshops codirected by the author at the Society for Education in Anesthesia Annual Meeting in 2011, the SPA Winter Scientific Meeting in 2012, and the International Assembly of Pediatric Anesthesia and the ASA Annual Scientific Meeting in Washington, DC, in 2012. Discussion This problem-based learning module facilitates group discussion with the integration of existing knowledge and new knowledge by self-directed learning in order to increase the quality of PBLDs.